PENGARUH LIKUIDITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI MODERASI - William William; Hendang Tanusdjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study was to determine the effect of liquidity and capital structure on firm value with profitability as a moderating variable in transportation and logistics companies listed on the Indonesia Stock Exchange in 2018-2020. Samples were taken based on predetermined criteria using purposive sampling method. The data that meet the criteria are 10 companies. The sample processing method uses moderated regression analysis (MRA) using E.views 12 application. The results obtained in this study are liquidity has a positive effect on firm value, capital structure has no effect on firm value, and profitability is only able to moderate the relationship between liquidity and value company. These results indicate that companies need to improve liquidity performance and pay attention to profitability performance in order to increase company value which will give a positive signal to investors.